ANALISIS PENERAPAN MODEL INKUIRI TERBIMBING TERHADAP KPS PESERTA DIDIK PADA MATERI GAYA DAN GERAK DI SMP ISLAM AS-SHOFA PEKANBARU - Khairanila, Khairanila; Azizahwati, Azizahwati; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract : Science process skills (SPS) are very important for students to face competition in a global era that demands competition between people. The reason for the lack of development of students' process skills is because teachers have not optimized the use of appropriate learning models and students have not been guided optimally when carrying out the learning process. However, science process skills can still be trained and improved through the use of models, strategies and learning approaches that are able to stimulate students' science process skills. This research was conducted by uto find out the analysis of the guided inquiry model on students' science process skills in the materialforce and motion on thingsin middle school. The type of research used isPre-Experimental Designwith a planOne Shoot Case Study that is, there is a given grouptreatment (treatment) in the form of applying the guided inquiry learning model and then the results post-test analyzed. This research was conducted at As-Shofa Islamic Middle School Pekanbaru in the odd semester of the 2023/2024 academic year. The research population was all class VIII students consisting of 4 classes with a total of 92 people. The sample was determined using the lottery technique so that class VIII.4 was obtained as the experimental class.Research data was collected by giving tests in the form ofposttest totaling 15 questions consisting of 5 PPP indicators were then analyzed descriptively. The research results from descriptive analysis show that students' absorption capacity after learning with the guided inquiry learning model is already in the medium category because some students have been able to complete the science process skills test well.Keywords : Guided Inquiry, Science Process Skills.